Rancang Bangun Sistem Keamanan Lalu Lintas Menggunakan Smartphone Dan Esp32cam Berbasis Arduino Mega 2560 - Putra, Okta Andrica; Handika, Rino (CV. Information Technology Training Center - Indonesia (ITTC), 2022)
Lots of vehicle users who ignore this traffic light. Even though there are a lot of risks that are faced if you ignore traffic lights, for example accidents due to directly passing a red light while at another intersection there are vehicles that are speeding, congestion is getting worse due to the difficulty of vehicles from the opposite direction to move forward, and so on. At this time, penalties for traffic violators are still using civil and criminal penalties. The motorist community is currently still arbitrarily with civil and criminal penalties given if they violate traffic rules, one of which is if they pass a red light. Motorists who violate are given a penalty of paying a fine on the spot or given a ticket for further processing in court. However, this does not provide a deterrent effect for motorists, so they often violate the same thing. This tool consists of several main components, namely Android Smartphone, ESP32CAM, Infrared Sensor, RTC, LDR Sensor, 16x2 LCD, RGB LED, Buzzer, DFPlayer Mini, Speaker, Water Pump, Lamp, Arduino Mega 2560 and this tool is programmed using Arduino app.